Perbandingan Pengujian Konsolidasi Menggunakan Alat Rowe Cell dan Oedometer pada Tanah Lanau Lunak - Iskandar; Rabiya (Potensi: Jurnal Sipil Politeknik, 2020)
Soil consolidation testing using an oedometer and rowe cell. Oedometers are often used on clay and soft soils. However, in the development of the rowe cell device, the results of lowering soft soil were better than the oedometer. The advantage of this rowe cell is that it can determine the saturation value of the soil samples tested. The rowe cell tester can measure the pore water pressure at the beginning and end of each consolidation stage. This rowe cell can provide suitable settlement for soft soils. This consolidation test to obtain soil parameters such as Cv and Cc by using the rowe cell tool. After that, from the test results, the two tools were compared.